2022
DOI: 10.1200/jco.2022.40.16_suppl.1060
|View full text |Cite
|
Sign up to set email alerts
|

Predicting hyperglycemia among patients receiving alpelisib plus fulvestrant for metastatic breast cancer.

Abstract: 1060 Background: Although hyperglycemia is recognized as a common adverse event (AE) on alpelisib (ALP), this AE has been little studied outside clinical trials. We report the frequency of ALP-associated hyperglycemia in a real-world setting and evaluate proposed risk factors. Methods: We retrospectively identified patients with PIK3CA-mutated, hormone receptor-positive, metastatic breast cancer who initiated treatment with ALP+fulvestrant (FUL) between August 2019 and December 2021. Five primary characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One retrospective study of 27 patients with metastatic PIK3CA-mutated breast cancer treated with alpelisib showed no difference in response to alpelisib according to BMI (p = 0.966), although the study was limited by the small sample size [112]. Other studies have shown that patients with increased BMI, pre-existing hyperglycemia, and prediabetes/diabetes are at increased risk of alpelisib-induced hyperglycemia [113,114]. Management strategies have been proposed to prevent and treat alpelisib-induced hyperglycemia, including counseling on healthy lifestyle behaviors, optimization of blood glucose prior to alpelisib treatment, and treatment with anti-hyperglycemia agents [111].…”
Section: Mtor/pi3k Inhibitorsmentioning
confidence: 99%
“…One retrospective study of 27 patients with metastatic PIK3CA-mutated breast cancer treated with alpelisib showed no difference in response to alpelisib according to BMI (p = 0.966), although the study was limited by the small sample size [112]. Other studies have shown that patients with increased BMI, pre-existing hyperglycemia, and prediabetes/diabetes are at increased risk of alpelisib-induced hyperglycemia [113,114]. Management strategies have been proposed to prevent and treat alpelisib-induced hyperglycemia, including counseling on healthy lifestyle behaviors, optimization of blood glucose prior to alpelisib treatment, and treatment with anti-hyperglycemia agents [111].…”
Section: Mtor/pi3k Inhibitorsmentioning
confidence: 99%
“…In addition, the function of macropinocytosis can provide amino acids to breast cancer cells by degrading proteins, which supports their survival and proliferation 105 . Two PI3K inhibitors in clinical trials, BKM120 106 and ZSTK474, and a US Food and Drug Administration‐approved drug, Alpelisib, 107,108 have been reported to suppress macropinocytosis. BKM120 completed a phase III clinical trial for breast cancer (NCT01610284).…”
Section: Therapeutic Implications Of Amino Acids In Breast Cancermentioning
confidence: 99%